Alpha-Alumina Extraction from Al-Ga'ara Bauxite - A . K. Mohammed, Abdul-Halim; Ibrahim, Ala; G. Madhhoor, Marwan (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The bauxite produced from Al-Ga 'ara area in Al-Enbar containing 50.4 wt. percentages Al2O3 was used for a- alumina production.                                                                                                For α-alumina production bauxite was mixed with calcium carbonate in a ratio 1:3 and the mixture was burned at temperature range 1l 50-l350°C, cooled to 500°C; crushed and ground. The powder produced treated then with 6% sodium carbonate solution using different temperature (60-100°C) for fifteen minutes. After filtration, the produced sodium alurninate solution was reacted with 2% of calcium hydroxide at 98°C for thirty minutes. The filtrate was carbonated with purified C02 gas at 70°C for different times (30-180 min) and different flow rates (20-80 cm3/min).Alumina was precipitated as hydrate, then washed with water, dried at 110°C, and calcined at 1200°C. The produced α Al2O3 was identified   by X-ray diffraction.